Training on Lesson Plan of Climate Change STEM Project in the Physics Learning for Sustainable Development - Lestari, Nurita Apridiana; Jatmiko, Budi; Hariyono, Eko; Dwikoranto, D; Prahani, Binar Kurnia (Universitas Lambung Mangkurat, 2025)
Climate change education holds great potential but often fails to raise sufficient awareness of climate-related disasters. Students need localized, STEM-based learning to build adaptation strategies and eco-friendly lifestyles. This article focuses on improving students' understanding of physics concepts, problem-solving, and critical and creative thinking, aligning with the SDGs and Merdeka Curriculum goals. Using the Participatory Action Research (PAR) method, training activities involved observation, reflection, planning, action, and evaluation stages. Needs analysis discussions with teachers from Nganjuk Regency's MGMP informed the program. Training included STEM-based project learning focused on climate change and engaging physics and science teachers. Questionnaire analysis showed high enthusiasm for the program, as it integrated STEM with real-world climate issues, making learning relevant and motivating. This innovative approach fostered critical thinking and problem-solving while enhancing awareness and responsibility toward climate challenges. By connecting education to sustainability, the program encouraged students to develop eco-friendly solutions and actively participate in addressing global issues, preparing them to become agents of change.